2006
DOI: 10.1590/s1516-35982006000500032
|View full text |Cite
|
Sign up to set email alerts
|

Inclusão de fontes de óleo na dieta de cabras em lactação: digestibilidade dos nutrientes e parâmetros ruminais e sangüíneos

Abstract: RESUMO -Os objetivos neste trabalho foram avaliar o efeito da inclusão de fontes de óleo na dieta de cabras em lactação sobre o consumo, a digestibilidade total dos nutrientes, a concentração de NDT e os parâmetros da fermentação ruminal. de óleos vegetais e de níveis de extrato etéreo superiores a 7% na MS da dieta não altera a digestibilidade dos nutrientes e os parâmetros de fermentação ruminal de cabras em lactação.Palavras-chave: óleo de arroz, óleo de canola, óleo de soja, pH ruminal Feeding vegetable oi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1
9

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 20 publications
0
5
1
9
Order By: Relevance
“…Milk yield decrement in studies by Martin et al (2008) in cows and Silva et al (2007) in goats by extra fat addition (5.7% in the diets of former study and 4.5% in those of latter) compared with animals given control diets without fat inclusion was parallel with DMI and fibrous carbohydrate digestibility. The DMI and milk production was similar with control diet but 24% decrease in NDF digestibility observed when diet included with 5.1% of soybean oils, rapeseed or rice (Maia et al, 2006a;2006b).…”
Section: Effect Of Supplemental Fat On Milk Yieldmentioning
confidence: 52%
“…Milk yield decrement in studies by Martin et al (2008) in cows and Silva et al (2007) in goats by extra fat addition (5.7% in the diets of former study and 4.5% in those of latter) compared with animals given control diets without fat inclusion was parallel with DMI and fibrous carbohydrate digestibility. The DMI and milk production was similar with control diet but 24% decrease in NDF digestibility observed when diet included with 5.1% of soybean oils, rapeseed or rice (Maia et al, 2006a;2006b).…”
Section: Effect Of Supplemental Fat On Milk Yieldmentioning
confidence: 52%
“…O efeito da inclusão de óleos na dieta ainda não está bem elucidado, visto que alguns autores verificaram redução no consumo (JENKINS &THIES, 1997;SILVA et al, 2007), enquanto outros não observaram influência do lipídio na dieta (MAIA et al, 2006;LANA et al, 2007).…”
Section: Resultsunclassified
“…Upon the addition of 5.1% oil (canola oil, rice and soybeans) to the diets of goats, which consisted of a forage: concentrate ratio of 50:50 and 7.83% fat content, Maia et al (2006) observed no changes in the N-NH 3 ruminal concentrations. However, they observed an increase in the pH, showing that addition of fat may alter ruminal fermentation patterns and microbial activity.…”
Section: Introductionmentioning
confidence: 98%